Effect of Human Immunodeficiency Virus (HIV) Type 1 Envelope Subtypes A and D on Disease Progression in a Large Cohort of HIV-1–Positive Persons in Uganda - Kaleebu, Pontiano; French, Neil; Mahe, Cedric; Yirrell, David; Watera, Christine; Lyagoba, Fred; Nakiyingi, Jessica; Rutebemberwa, Alleluiah; Morgan, Dilys; Weber, Jonathan; Gilks, Charles; Whitworth, Jimmy (The Journal of Infectious Diseases, 2002)
The effect of human immunodeficiency virus (HIV) type 1 envelope subtypes A and D on disease progression was investigated in 1045 adults in Uganda. At enrollment and every 6 months, a clinical history, examination, and laboratory investigations that included CD4 cell counts were done. HIV-1 envelope subtype was assessed mainly by peptide serology supplemented by heteroduplex mobility assay and DNA sequencing. A multivariate analysis of survival was performed to assess the prognostic value of HIV-1 subtype on death. A marginal general linear model also determined the effect of subtype on CD4 cell count during follow-up. Subtype D was associated with faster progression to death (relative risk, 1.29; 95% confidence interval, 1.07–1.56; P ¼ .009) and with a lower CD4 cell count during follow-up (P ¼ .001), compared with subtype A, after adjusting for CD4 cell count at enrollment. In Africa, envelope subtype D is associated with faster disease progression, compared with subtype A
Keywords: HIV; Africa; CD4 count dtermination; Disease progression; Follow up; HIV-1; sequence analysis